Red-Emissive Cell-Penetrating Polymer Dots Exhibiting Thermally Activated Delayed Fluorescence for Cellular Imaging - Christopherson, Cheyenne J; Paisley, Nathan R; Xiao, Zhujun; Algar, W. Russ; Hudson, Zachary M (Journal of the American Chemical Society, 2021)
Fluorescence imaging in living cells is key to understanding many biological processes, yet autofluorescence from the sample can lower sensitivity and hinder high-resolution imaging. Time-gated measurements using phosphorescent metal complexes can improve imaging, at the cost of potential toxicity from the use of heavy metals. Here, we describe orange/red-emitting polymer dots (Pdots) exhibiting thermally activated delayed fluorescence (TADF) for time-gated imaging. Inspired by the cell invasion mechanism of the HIV TAT protein, the Pdots were formed from block copolymers composed of a hydrophilic guanidine-rich block as a cell-penetrating peptide mimic, and a rigid organic semiconductor block to provide efficient delayed fluorescence. These all-organic polymer nanoparticles were shown to efficiently enter HeLa, CHO, and HepG2 cells within 30 min, with cell viabilities remaining high for Pdot concentrations up to 25 mg mL–1. Pdot quantum yields were as high as 0.17 in aerated water, with the Pdot structure effectively shielding the TADF emitters from quenching by oxygen. Colocalization experiments revealed that the Pdots primarily accumulate outside of lysosomes, minimizing lysosomal degradation. When used for fixed cellular imaging, Pdot-incubated cells showed high signal-to-background ratios compared to control samples with no Pdot exposure. Using time-resolved spectroscopy, the delayed emission of the TADF materials was effectively separated from that of both a biological serum and a secondary fluorescent dye.